The Factors Influencing Brand Love and Willingness to Pay among iPhone Consumers in Indonesia - Efrita Soviyanti; Nofrizal Nofrizal (Bina Nusantara University, 2024)
The iPhone has become a globally exclusive and luxurious item, including in Indonesia, and it even serves as a high social status symbol for its owners. Almost every launch of a new series product always garners attention and sells out, despite its high price compared to competitors with slightly different specifications. The research aimed to identify the factors influencing brand love and willingness to pay among iPhone consumers in Indonesia. Consumer behavior and personality factors, such as social status, self-expression, hedonism, and perceived quality, were utilized as determinant variables of brand love and willingness to pay. A total of 654 iPhone users participated in filling out surveys on social media, in Apple stores, and through online forms via Google Forms. Smart-PLS 4.0 software was employed for statistical data analysis, utilizing Partial Least Squares - Structural Equation Modeling (SEM-PLS). In the results, it is proven that the positive factors driving iPhone customers’ brand love come from perceived quality, social status, and self-expression. Meanwhile, the factors driving willingness to pay are brand love, perceived quality, social status, and self-expression. However, hedonism does not have a positive impact on brand love and willingness to pay. The research results suggest that the hedonic experience of the product may not be the main factor influencing consumers in the context of premium products such as the iPhone. The strong and luxurious branding of iPhone is the main reason for its customers. In addition, brand love is a key variable that mediates willingness to pay.